Library Literacy Program: an information access tool for undergraduate student in Multimedia University / Mohd Ridzuan Ibrahim - Ibrahim, Mohd Ridzuan (2002)
The purpose of this project was to create an information literacy program for undergraduate student at MMU. The research undertaken supported the development of written materials, such as guides or guidelines for faculty and students. Recommendations resulting from the project are to be used to instruct the faculty regarding the components and requirements of the information literacy program. Assessment tools and competencies for all course work in the undergraduate year. A strategic plan is recommended along with a faculty development plan and a time line. This project utilizes the development problem -solving process. This include the description of the problem, the collection of data through research and observation, the development and implementation of product to correct the problem, and the specifications for evaluation of the product.